Touring the carbon ruins : Towards an ethics of speculative decarbonisation - Raven, Paul Graham ; 0000-0002-3555-843X; Stripple, Johannes (The Trouble with Speculation : Natures, Futures, Politics, 2024)
For many years, questions about the future have been marginalised within the social sciences: asking how we might live in a post-fossil society, or what are the key decisions and events that could take us there, has been seen as outside of the disciplinary scope. In this chapter – which takes as its point of departure the ‘speculative turn’ that is increasingly inspiring a range of works, from foresight scenarios to design fiction – we insist on the need to invent methods and practices which provide speculative spaces that allow such questions to be articulated. We use our own speculative initiative, ‘The Museum of Carbon Ruins’, to foreground a series of ethical questions that accompany such speculative endeavours, but which have so far been neglected in contemporary discussions. Working within a critical utopian modality, Carbon Ruins does not foreclose ethical possibilities, but allows citizens to grapple with, evaluate, amend and critique the post-fossil futures that official policy is striving towards.